Viral Therapy of Human Cancers - Sinkovics, Joseph G. (Taylor and Francis, 2004)
Featuring contributions from nearly 30 leading authorities, this pioneering work gauges the potential for viruses to act as oncolytic and anti-tumor agents for the treatment of cancers in humans-detailing the cancer-combative properties exhibited by viruses in nature, genetically engineered viruses, and viral oncolysates as evidenced in basic and experimental studies
Description based upon print version of record
Keywords: Electronic books